Penggunaan Media Papan Flanel Dalam Meningkatkan Pemahaman Mengenal Warna Dalam Bahasa Arab Pada Siswa TK Tholabul Hikmah Kecamatan Taman Kabupaten Pemalang - Srifariyati Srifariyati; Oka Prasasti (JURNAL PENDIDIKAN ROKANIA, 2023)
ABSTRACT Color is an element of beauty. Bright colors are very liked by children. However, not all children know the names of colors in Arabic with limited learning media. The use of flannel board media is needed in learning to recognize colors in Arabic. This study aims to describe the use of flannel board media in improving understanding of color in Arabic. The type of research used in this research is qualitative. The research subjects were groups B1 and B2, with a total of 43 students from the Tholabul Hikmah Kindergarten Taman, Pemalang. The method used in this study is experimental research. The results of this study are the percentage of students' initial ability to recognize colors in Arabic by not using flannel board media is 18.15%. While the percentage of students' ability to recognize colors in Arabic after using flannel board media is 25.12%. Then there is an increase in understanding from not using a flannel board by using a flannel board by 6.97%. It can be concluded that the students' ability to understand colors in Arabic using flannel board media has increased greater than before using flannel board media.